Usefulness of Strouhal number in evaluating human under-water undulatory swimming - Arellano, R.; Pardillo, S.; Gavilan, A. (2002)
The Strouhal number is a dimensionless number, representing the ratio of unsteady and steady motion. Strouhal number (St) is defined by the equation: St = Ap -p f / U, where = Ap -p is the tail-beat peak-to-peak amplitude (the distance from the peak of the tail fluke upstroke to the peak of the tail fluke downstroke; Ap -p = 2h), f the stroke frequency (Hz) and U the swimming velocity (Fish & Rohr, 1999). Strouhal numbers for swimming fish and dolphins were between 0.25 and 0.35, as predicted by the theory described by Triantafyllou (1993) in maximum efficiency situations. The purpose of the study was to compare the values of an adapted Strouhal number (StN) between swimmers of different level of performance during undulatory underwater swimming.